Smaller-incision new-generation implantable miniature telescope in late-stage age-related macular degeneration: 6 month outcomes - Mario Damiano Toro; Alfonso Savastano; Faustino Vidal Aroca; Paola Sasso; Giuseppe Francione; Gaetano Fioretto; Marina Montemagni; Claudio Xompero; Nicola Claudio D'Onofrio; Ciro Costagliola; Stanislao Rizzo (Heliyon)
Purpose: To evaluate the intermediate-term visual and safety outcomes of the small-incision second-generation implantable miniature telescope (SING IMT) in patients with late-stage age-related macular degeneration (AMD) at 6 months post-surgery. Design: Retrospective cohort study. Methods: Medical records of patients implanted with the SING IMT at two sites in Italy were reviewed. Outcomes evaluated up to 6 months post-surgery included best-corrected distance (BCDVA) and distance-corrected near (DCNVA) visual acuity, intraocular pressure (IOP), anterior chamber depth (ACD), corneal endothelial cell density (ECD), and adverse events. Results: The study involved 35 patients (mean age: 77.4 years). At 6 months post-surgery, the mean ± standard deviation (SD) change in BCDVA from baseline was −0.29 ± 0.142, and at least 1-, 2-, and 3-line gains in BCDVA were achieved in 97.1 %, 68.6 % and 51.4 %, of operated eyes, respectively. The percentage of patients able to read at near distance increased from 28.6 % at baseline to 97.1 % at 6 months post-surgery with a mean improvement of −0.57 ± 0.206. No clinically meaningful change from baseline was observed in terms of IOP or ACD. The mean (SD) change from baseline in ECD at 6 months in operated eyes was −280.7 (315.9) cells/mm2 (−11.4 %). The most frequent adverse event was corneal edema, and all cases were resolved with topical medications. Conclusions: This intermediate-term assessment confirms that SING IMT implantation improved distance and near vision, with a low impact on the corneal endothelium and an acceptable and manageable rate of complications and adverse effects.